2021
DOI: 10.1097/fpc.0000000000000430
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics: a perspective and preparedness of Pharm-D and medical students in Jordan

Abstract: Background Pharmacogenetics (PGx) science has evolved significantly with a huge number of studies exploring the effect of genetic variants on interindividual variability of drug response. In this study, we assessed the knowledge, attitudes and preparedness of Pharm-D vs. medical students toward PGx. Method A paper-based cross-sectional survey was performed. A pilot-tested questionnaire consisting of 21 questions (demographics 5, knowledge 6, attitude 6,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…45 As compared to Jordan, medical and pharm-D students showed similar pattern in terms of insufficient PGx knowledge as well as low preparedness levels to conduct these tests while maintaining overall positive attitudes. 46 In agreement to the above studies, medical students in the United States (US), stated that only 29.8% of them had covered a genetic course, and those who took a genetic course were found to be more likely to be confident and comfortable to deal and answer questions related to PGx. 47 Similar outcomes were documented across the health professional who are involved in practice in UAE in regard to their interest and attitudes.…”
Section: Knowledge and Attitudes Of Physicians And Pharmacists Toward...mentioning
confidence: 73%
See 1 more Smart Citation
“…45 As compared to Jordan, medical and pharm-D students showed similar pattern in terms of insufficient PGx knowledge as well as low preparedness levels to conduct these tests while maintaining overall positive attitudes. 46 In agreement to the above studies, medical students in the United States (US), stated that only 29.8% of them had covered a genetic course, and those who took a genetic course were found to be more likely to be confident and comfortable to deal and answer questions related to PGx. 47 Similar outcomes were documented across the health professional who are involved in practice in UAE in regard to their interest and attitudes.…”
Section: Knowledge and Attitudes Of Physicians And Pharmacists Toward...mentioning
confidence: 73%
“…The overall percentage knowledge score was poor with a score of 46.7%. 46 In Syria, a recent study evaluated physicians and pharmacist's knowledge concerning PGx. Years of experience had no impact on the knowledge levels between both groups.…”
Section: Pharmacogenetics Knowledge and Attitude Of Physicians And Ph...mentioning
confidence: 99%
“…In comparison, most studies with pharmacy students found a good or fair level of knowledge among most participants. 69 , 73 , 74 , 76 , 77 , 78 , 79 , 80 , 81 Some studies only reported self‐assessed (subjective) knowledge of PGx, which was generally reported as “low.” However, self‐assessed knowledge did not always correlate with actual expertise in studies that assessed both. 37 While many studies did not report data on “biological sex,” one study noted a difference in the knowledge level of pharmacy students between males and females.…”
Section: Resultsmentioning
confidence: 99%
“…In comparison, most studies with pharmacy students found a good or fair level of knowledge among most participants. 69,73,74,[76][77][78][79][80][81] Some studies only reported self-assessed (subjective) knowledge of PGx, which was generally reported as "low." However, self-assessed knowledge did not always correlate with actual expertise in studies that assessed both.…”
Section: Knowledge and Awareness Of Pgxmentioning
confidence: 99%
“…In a survey of health sciences and other university students, Siamoglou and colleagues found that the students held positive attitudes towards PGx and its benefits on disease management, drug efficacy, and reduction of adverse effects [ 12 ]. Zawiah and colleagues found strong support from pharmacy and medical students of PGx testing to help to decrease adverse events, optimize drug dosing and improve drug efficacy [ 13 ]. The majority of these students did not agree that they were competent to discuss PGx information with other providers, or that they could accurately apply PGx test results.…”
Section: Introductionmentioning
confidence: 99%